Splenic non parasitary cyst. - Ferreira, Nelson; Ferreira, Ciro; Falconi, Luis (Cirugía del Uruguay, 1985)
Reporting a case of lienal pathology of such extremely rare occurrence as the epidermoid type non parasitary cyst, establishing diagnostíc and histogenetic consíderalíons.